THE INFLUENCE OF WORK STRESS, WORKLOAD AND WORK ENVIRONMENT ON THE PERFORMANCE OF HEALTH WORKERS AT THE SIABU COMMUNITY HEALTH CENTER, MANDAILING NATAL REGENCY - Nurul Azizah; Em Yusuf Iis; Aiyub; Likdanawati (RADJA PUBLIKA, 2025)
This study investigates the influence of job stress, workload, and work environment on the performance of health workers at UPTD Puskesmas Siabu, Mandailing Natal Regency. A quantitative research method with a descriptive associative approach was applied. Data were collected using a questionnaire and analyzed through multiple linear regression. The findings indicate that job stress, workload, and work environment have both simultaneous and partial significant effects on health workers’ performance. The results emphasize the importance of managing workplace stress, balancing workloads, and improving the work environment to enhance overall performance.